Laboratory Tests of the Interaction Zone between Reinforced Soil Components - Andrzej Surowiecki; Marek Kopinski (Communications - Scientific letters of the University of Zilina, 2002)
Laboratory investigation results related to the range of the interaction zone between a non-cohesive soil medium and vertically positioned reinforcement inserts are discussed. The investigations consisted of the measurement of the composite’s side pressure; they have been carried out on large-scale models of subsoil (sand, gravel, grit) with reinforcements in the form of metal and plastic nets. It has been proved that the vertical range of the reinforcement effect zone depends upon characteristics of the soil medium and reinforcement parameters.